A Pioneering Patient Lift: Prevention of Low Back Pain in Health Care Workers in the 18th Century. Issue 2 (15th January 2015) - Manzini, Francesco; Cesana, Giancarlo; Manzini, Claudio; Riva, Michele Augusto
Abstract : Level of Evidence: 5 Abstract : The use of a patient lift was first described in the 18th century. This device was developed for helping monks in changing bedclothes of sick and disabled people. A pioneering patient lift in the 18th century may be considered as an important milestone in spinal disorders prevention research.